If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4x + 5) = 0 Reorder the terms: 3(5 + 4x) = 0 (5 * 3 + 4x * 3) = 0 (15 + 12x) = 0 Solving 15 + 12x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15' to each side of the equation. 15 + -15 + 12x = 0 + -15 Combine like terms: 15 + -15 = 0 0 + 12x = 0 + -15 12x = 0 + -15 Combine like terms: 0 + -15 = -15 12x = -15 Divide each side by '12'. x = -1.25 Simplifying x = -1.25
| -5(8x-6)= | | 3m^3+30m+75=0 | | 8-(5+3x)=14 | | -8x^2+8x+5=5 | | 4m^2+4=-8m | | x+x=160000 | | x+x^20+68=248 | | 6w-14=4w+14 | | X+12=5x | | -38=2-(-43d-24) | | 14y+4=16y-8 | | 2(2x+4)=4x+8 | | 4z+32=6z-2 | | x^2-9x+36=0 | | 5(x-6)=3x-14 | | 35x^2+42x+12=0 | | 4x^2=2x-5 | | 6z-2+2z+16=90 | | 6z-2=2z+16 | | 2z+16=6z-2 | | 239-3x=42x+19 | | (10x+5)(x-9)=0 | | 83-4x=41x+23 | | 123-5x=2x+18 | | (5-y)+(6-7)-(5-y)=0 | | x(4)=-6 | | t^2+17=-8t | | 71-7x=2x+20 | | 7-6x=139-37x | | 2x+3x-12x= | | 4x+8=-80-7x | | -12-4x=13-4x |